Administration of Castanea sativa flowers extract in Wistar rats - Nascimento-Gonçalves, Elisabete (2019)
Castanea sativa Mill. flowers (CF) are reported by ancestral claims as having health benefits like mucolytic, antispasmodic and anti-dysenteric properties and, in vitro studies showed anticancer properties against breast, colon, cervical and hepatocellular carcinomas [1]. The aim of this work was to study the effect of chestnut flowers (CF) extract on rat’s physiological parameters. Fifteen male Wistar Unilever rats were randomly divided into two groups: untreated control, n=10, and CF group, n=5. Animals from CF group were exposed to the chestnut flowers extract in drinking water (20 mg/animal/day) for 49 weeks. Body weight, food and drink consumption were measured weekly. At necropsy, all organs were collected, weighed and liver and kidney were processed for histological analysis. Animals from CF group showed a mean final body weight and a food consumption higher than untreated animals (p>0.05). Animals from CF group showed lower consumption of water (p=0.000). Relative mean liver weight from animals treated with CF was higher than untreated animals (p=0.026) and presented more liver degeneration. However, liver inflammatory infiltrate was reduced (p=0.026) in animals exposed to CF extract. There were no significant differences in relative mean kidney weight among groups. Untreated animals developed 50% of discrete proteinuria and CF treated animals developed 20%. Serum levels of albumin, total protein, glucose and alanine aminotransferase did not show significant differences between experimental groups. These results suggest that chestnut flowers extract was well tolerated by the animals, did not cause hepatic and kidney toxicity and had no effect on biochemical profile. Further studies are necessary to evaluate in vivo, the effect of different CF doses and evaluate the respective potential use.